Perception of Students and Teachers Towards Tribhuvan University Examinations - Sharma, Netra Prasad (Tribhuvan University Journal, 2016)
Tribhuvan University (TU), the oldest university in the country, was founded in 1959. It administered the first examinations in 1961. Since then it has come a long way and it has been conducting several examinations under both semester and annual systems. Nevertheless the standards of the examinations have raised questions among the stakeholders. Therefore, this article makes an attempt to find out what students and teachers have to say about the examinations conducted by TU. For this, a questionnaire based on the Likert Scale was used. The tool consisted of altogether 39 statements grouped under ten different constructs related to the standards of TU examinations. The tool was administered to 40 students and 10 teachers selected based on nonrandom sampling from the two campuses of TU located in Kathmandu. On the analysis of the responses, it was found that both students and teachers felt that there were shortcomings in TU examinations and that improvement were required in line with the internationally practiced standards of examinations.